Performance analysis of supercritical pressure CO2 in several enhanced tubes with non-uniform heat flux. (5th November 2020) - Zhang, Haiyan; Guo, Jiangfeng; Cui, Xinying; Huai, Xiulan
Highlights: Four novel enhanced tubes were proposed for non-uniform heat flux conditions. Non-uniformity of wall temperature can be abated greatly with enhanced tubes. Secondary flow plays an important role in horizontal non-uniformly heated tubes. Coordination distribution principle interprets the heat transfer in tubes well. Abstract: Non-uniform heat flux conditions complicate the flow and heat transfer performance in tubes, especially when supercritical fluids are employed. In the present study, four novel tubes with local ribs or concaves were proposed, and thermal–hydraulic characteristics of supercritical pressure CO2 in the four tubes with non-uniform heat flux were investigated numerically. A maximum improvement of 25.61% in heat transfer coefficient can be obtained while the friction factor only increases about 11.81% with the employment of enhanced tubes. Based on a self-defined non-uniformity of wall parameters, efficient reductions of wall temperature and heat flux non-uniformities in enhanced tubes were observed. The secondary flow caused by buoyancy in horizontal tubes plays crucial roles in heat transfer characteristics. The ratio of the secondary flow number to Reynolds number Se/Re could give great predictions for the buoyancy effect in tubes with non-uniform heat flux. In addition, the coordination angle between the vectors of local heat transfer coefficient and local temperature difference is closely associated with the heat transfer uniformity and can provide a new understanding for the heat transfer mechanism in non-uniformly heated tubes.